A participação da extensão universitária no processo de descolonização do pensamento e valorização dos saberes na América Latina - Maria das Dores Pimentel Nogueira (2019)
This thesis aims to contribute to the understanding of how university extension can resist and deconstruct the logic of colonization, contributing to the decolonization of Latin American thought and the valorization of local and regional knowledge. And also, to verify how the university extension can act to bring the local knowledge and other epistemes to the academic milieu, and, in addition, to contribute to the recognition of these knowledge. In order to achieve this, it was sought to know and understand how the university extension was built in Latin America, from 1908 to 2018. Based on the regional scope, two specific experiences were chosen: the Federal University of Minas Gerais (UFMG) in Brazil, and the National University of Cordoba (UNC) in Argentina. Both stand out not only in Brazil and Argentina, but also as models of university extension in the other Latin American countries. To carry out the research, a qualitative methodology was adopted, using techniques such as research and documentary analysis, as well as field research with semi-structured and in-depth interviews with key actors who worked on the construction of university extension and/or on the critical reflection on their role, identified at UNC and UFMG: rectors, extension secretaries, program coordinators and extension partners. The analysis of extension programs that work in the perspective of interculturality and the dialogue of knowledge revealed that in both countries there are regulatory frameworks that incorporate concepts and recommendations emanating from international bodies such as the UN, ILO and OAS, which recognize diversity of cultures and respect for other forms of knowledge as educational guidelines, as part of the so-called multicultural or intercultural policies. In this perspective, the Programs “Diversidad Cultural”, at UNC, and “Saberes Plurais”, at UFMG, found a favorable environment for their conception and execution, presenting significant results and impacts in the scope of diversity and the dialogue of knowledge. The analysis carried out throughout the thesis revealed that, in Brazil and Argentina, the university extension is the academic dimension that can open the way to the presence of diversity and interculturality in the university. Through extension actions, it is possible to know and recognize diversity, to carry out dialogues between traditional and academic knowledge, and to promote interculturality, without hierarchizing of cultures. It is possible, then, to make a university extension that is configured as resistance and acts in the deconstruction and decolonization of the imaginary and in the valorization of local and regional knowledge in Latin America. At UFMG and UNC this process has already started and has presented promising results. It is now necessary to consolidate experiences and disseminate them to the whole continent.